Classifying etiology of infantile spasms syndrome in resource‐limited settings: A study from the South Asian region. Issue 4 (25th October 2021) - Wanigasinghe, Jithangi; Sahu, Jitendra Kumar; Madaan, Priyanka; Fatema, Kanij; Linn, Kyaw; Chand, Prem; Poudel, Prakash; Hamed, Esmatullah; Mynak, Mimi L.; Hassan, Samaahath
Abstract: Objective: Etiological classification of infantile spasms syndrome (ISS) is important, considering the influence on prognosis based on the presence or absence of a known etiology. This study was performed to describe the limitations and difficulties experienced within the South Asian region when classifying the etiology of ISS according to the current recommendation. Method: Data on healthcare indices and facilities related to management of ISS for the nine countries in the South Asian region were gathered by the South Asian West Syndrome Research Group. A Google survey was performed among three hundred and thirty pediatric neurologists in the region. The capacity within each country for investigating etiology of ISS according to current described benchmarks was evaluated. The difficulties experienced in this regard and the potential solutions were investigated. Results: One hundred and sixty pediatric neurologists (response rate 48%) from Bangladesh (19/25), India (94/255), Myanmar (11/11), Nepal (6/8), Pakistan (19/25), and from Sri Lanka (7/8) responded. Three countries had no pediatric neurology services. Fifty‐six percent attempted to classify ISS etiology according to classification outlined by International League Against Epilepsy in 2017. The facilities to perform metabolic, genetic, and immunological investigations were very limited. Lack of funding for investigations and poor laboratory support were the two most frequent barriers encountered. Sixty percent indicated that a separate classification is suitable for low‐income setting; 78% suggested inclusion of separate category as "incompletely investigated" as an alternative solution to mitigate the barrier of achieving a better understanding of the etiological subtypes seen more frequently in this region. Significance: The resources in South Asian region are limited to meet the recommendations for investigating etiology of ISS. Including the etiological subcategory "incompletely investigated" is proposed as an alternative to understand the true proportions of children in this region, with a definite known etiology and those with an unknown etiology.